COMPARATIVE ANALYSIS OF RUSSIA’S AND CHINA’S PARTICIPATING IN GLOBAL GOVERNANCE INSTITUTIONS EXPERIENCE - Vladimir E. Petrovskiy (Сравнительная политика, 2015)
Article retractedThe article deals with the comparative analysis of Russian and Chinese participation in the current system of global governance, and in its reform. The author views participation of the respective countries in the system of global governance as part of their foreign policy and foreign policy strategy. He shows common and distinctive features of conceptual and practical approaches towards global governance defined by specific features of Russia’s and China’s history, economic development, political culture and traditions. Based on this comparative analysis, the author speculates on the future trends of participation of the two countries in the global governance system, in the spheres of global economy and international security, and on the future trends of their policy coordination in these respective areas.